VD_FINDINFO Arrêt / 2013 / 751 vom 4. Dezember 2013 - VD Tribunal cantonal (2013)
ADMISSION DE LA DEMANDE, AUTORITÉ PARENTALE, DROIT D'ÊTRE ENTENDU, ENQUÊTEEN GÉNÉRAL | 298a al. 2 CC, 446 CC, 450 CC, 15 LVPAE